TINGKAT KESIAPAN MASYARAKAT PENGELOLAAN LINGKUNGAN DAN KEPARIWISATAAN ALAM PASCA-ERUPSI 2010 - Muhamad Muhamad (Jurnal Kawistara, 2015)
This study aims to assess and measure the level of community preparedness southern slopes of Merapi eruption after 2010. Readiness level of environmental management and nature based tourism to approach local potential values. The higher the level of community preparedness in managing the environment and natural tourism high semakain the readiness level of the index value.